(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we introduce a new class of multivalued contractions and prove the existence of a fixed point for such contractions. Some consequences are presented in b-metric spaces endowed with partial order or with graph. To illustrate the applicability of our results, we offer an example and an application to the existence of solutions of an integral inclusions.